2006
DOI: 10.1515/bc.2006.057
|View full text |Cite
|
Sign up to set email alerts
|

Role of the kinin B1 receptor in insulin homeostasis and pancreatic islet function

Abstract: Kinins are potent vasoactive peptides generated in blood and tissues by the kallikrein serine proteases. Two distinct kinin receptors have been described, one constitutive (subtype B2) and one inducible (subtype B1), and many physiological functions have been attributed to these receptors, including glucose homeostasis and control of vascular permeability. In this study we show that mice lacking the kinin B1 receptor (B1-/- mice) have lower fasting plasma glucose concentrations but exhibit higher glycemia afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…Evidence that kinins induce insulin sensitivity in adipocytes (20) and control insulin released by pancreatic cells (21,22) indicates that the kallikrein-kinin system also participates in metabolic processes. However, the physiological relevance of this system to energy homeostasis and the contributions of the kinin B 1 receptor to these processes are still not well understood.…”
mentioning
confidence: 99%
“…Evidence that kinins induce insulin sensitivity in adipocytes (20) and control insulin released by pancreatic cells (21,22) indicates that the kallikrein-kinin system also participates in metabolic processes. However, the physiological relevance of this system to energy homeostasis and the contributions of the kinin B 1 receptor to these processes are still not well understood.…”
mentioning
confidence: 99%
“…Ara ú jo et al (2006) verified that B1 -/-mice have pancreatic abnormalities, such as fewer islets of Langerhans and lower glucose-triggered insulin release. They also observed that the endogenous B1 agonist des-Arg9-bradykinin (DBK) stimulates insulin release in vivo in wild type mice by increasing pancreatic vascular permeability (Ara ú jo et al, 2006 ).…”
Section: Introductionmentioning
confidence: 98%
“…In renal inflammatory conditions such as AKI, the kallikrein-kinin system (KKS) plays an important role in glucose homeostasis [5,6] . This system is also involved in kidney inflammatory and vasodilation processes [7] , which are directly involved in the inflammatory response mechanism of AKI.…”
Section: Introductionmentioning
confidence: 99%